Collaborative Learning Sebagai Model Inovasi Pendidikan Dalam Pembelajaran - Munfiatik, Siti (Yayasan Miftahul Ulum Sangatta Kutai Timur (KEP. MENKUMHAM RI No. AHU-0014779.AH.01.04.Tahun 2018) bekerjasama dengan Jurusan Tarbiyah STAI SANGATTA Kab. Kutai Timur., 2023)
The aim of this research is to understand in depth the concept of Collaborative Learning and the process of implementing it in a learning context, as well as identify obstacles that arise and find appropriate solutions to overcome them. The method used is the library research method. The result is the concept of Collaborative Learning as a model of educational innovation in learning that emphasizes cooperation and collaboration between students to achieve joint learning goals that can encourage social interaction, active involvement, and joint knowledge construction. The process of implementing Collaborative Learning involves planning, implementation, and evaluation stages by planning carefully, forming student groups, choosing appropriate methods, and providing support during the learning process. The problems are: social interaction problems, inequality within groups, resistance to collaboration, or technical obstacles. Solutions offered include social skills training for students, support from teachers or facilitators, and adjustments to learning methods to meet student needs. It is hoped that by understanding the concept of Collaborative Learning, understanding the process of implementing it, and identifying and overcoming obstacles that may arise, this research can provide valuable insight to educators, students, and other educational stakeholders about how to maximize the benefits of Collaborative Learning as a form of educational innovation. in learning.